2010
DOI: 10.1007/s11802-010-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and gear characteristics of the Macrobrachium fishery of the Cross River Estuary, Nigeria

Abstract: The Cross River Estuary, Nigeria, is an important shrimping area for artisanal fishermen of the coastal communities. The multi-species Macrobrachium fishery is exploited with three main gears, namely beach seine, push net and trap. Studies on species composition of this fishery recorded thirteen shrimp species, one swimming crab (Callinectes amnicola) and two fish species (Eleotris sp. and Pellonula leonensis). The shrimp species identified included Macrobrachium macrobrachion (83.39% and 55.69% by number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Others are croaker spp and tonguesole with 0.990 and 0.950 EE values respectively. These values agree with the report of high exploitation of bonga by Ama-Abasi and Macrobrachium spp by Nwosu in the Cross River system [21,25]. According to Ama-Abasi, when comparing his work with that Moses, there was a severe decline in total catch after a 25-year period, as evidenced by declining catch rates as well as increasing mortality rates indicating that bonga fishery is under high pressure with the attendant socio-economic implications [16,25].…”
Section: Features Of the Cross River Estuarysupporting
confidence: 86%
See 2 more Smart Citations
“…Others are croaker spp and tonguesole with 0.990 and 0.950 EE values respectively. These values agree with the report of high exploitation of bonga by Ama-Abasi and Macrobrachium spp by Nwosu in the Cross River system [21,25]. According to Ama-Abasi, when comparing his work with that Moses, there was a severe decline in total catch after a 25-year period, as evidenced by declining catch rates as well as increasing mortality rates indicating that bonga fishery is under high pressure with the attendant socio-economic implications [16,25].…”
Section: Features Of the Cross River Estuarysupporting
confidence: 86%
“…According to Ama-Abasi, when comparing his work with that Moses, there was a severe decline in total catch after a 25-year period, as evidenced by declining catch rates as well as increasing mortality rates indicating that bonga fishery is under high pressure with the attendant socio-economic implications [16,25]. Also Nwosu reported that Macrobrachium macrobrachion had high fishing mortality of 7.09/year and exploitation rate (E) of 0.74 for males with fishing mortality of 6.05/year and exploitation rate (E) of 0.66 for females [21]. The study Macrobrachium spp annual production of 99.43 tonnes of Macrobrachium spp with annual yield of 62.32 tonnes, and annual biomass of 13.6 tonnes.…”
Section: Features Of the Cross River Estuarymentioning
confidence: 99%
See 1 more Smart Citation
“…Other scientific observations revealed that M. vollenhovenii occupies a wide range of habitats ranging from coastal brackish water to upstream riverine environments which provide the prawn with potentials for local adaptations (Jimoh et al, 2013). Nwosu, (2000) reported that specimen attaining adult sizes of up to 190mm were collected in Cross River Estuary, Nigeria. Food and Agricultural Organization of the United Nations (F.A.O., 2000) report opined that M. vollenhovenii can be equated in quality attributes to the widely cultured M. rosenbergii.…”
Section: Introductionmentioning
confidence: 99%